(untitled) (Journal of Comilla Medical College Teachers’ Association, 2025)
Background: Vitamin D is one of the important immunomodulator which enhance immune system of the body. The level of vitamin D directly influences the outcome of COVID-19 patients. Our study was carried out to explore the relationship between the level of vitamin D and COVID-19 positive patients and their outcome. Methods: We conducted a cross-sectional study of Covid positive patients from 1st June to 30 August 2020 whom got admitted at the Combined Military Hospital (CMH), Dhaka to assess vitamin D levels in COVID-19 patients. Diagnosis of COVID-19 was confirmed via viral Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) from nasal or nasopharyngeal swab or supporting radiological investigations. This study includes assessed demographic laboratory analysis, including vitamin D measurement. Data were collected from medical records and recorded in a questionnaire for analysis. Results: The 71 individuals included in this study had test results for Covid-19 in 2020 and vitamin D levels in pandemic period. Among 71 patients 34(48%) of patients were male and 37(52%) of patients were female, 28(39%) COVID19 positive patients had insufficient vitamin D, 37(52%) of patients had deficient vitamin D and 6(9%) of patients had adequate level of vitamin D. The duration of hospital stay was more (>14 days) among vitamin D deficient patients than patients with insufficient and adequate vitamin D level. The aged group (59-68years) suffered more in vitamin D deficiency than other age groups. Female patients were found more (54%) vitamin D deficient compared to male (46%). Conclusion: Vitamin D deficiency increases the chance of disease severity after COVID -19 infections. Vitamin D plays a protective role against Covid-19 infection. J Com Med Col Teachers’ Asso July 2025; 29(2): 94-97